2016
DOI: 10.1123/jpah.2016-0321
|View full text |Cite
|
Sign up to set email alerts
|

Results From the United States of America’s 2016 Report Card on Physical Activity for Children and Youth

Abstract: Background The 2016 U.S. Report Card on Physical Activity for Children and Youth provides a comprehensive evaluation of physical activity levels and factors influencing physical activity among children and youth. Methods The Report Card includes 10 indicators: overall physical activity, sedentary behavior, active transportation, organized sport participation, active play, health-related fitness, family and peers, school, community and the built environment, and government strategies and investments. National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
106
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(113 citation statements)
references
References 29 publications
4
106
0
3
Order By: Relevance
“…There are several factors which have been identified specifically affecting children's PA participation. These determinants include individual factors (ie, age, sex, weight status, socioeconomic status), interpersonal factors (ie, cultural and social), and environmental factors (ie, screen time, accessibility to sports equipment and playground) . As mentioned earlier, studies have shown that a decline in PA is prominent with age, and an increase in sedentary behaviors during adolescent years .…”
Section: Differences Between Latino and White Childrenmentioning
confidence: 99%
“…There are several factors which have been identified specifically affecting children's PA participation. These determinants include individual factors (ie, age, sex, weight status, socioeconomic status), interpersonal factors (ie, cultural and social), and environmental factors (ie, screen time, accessibility to sports equipment and playground) . As mentioned earlier, studies have shown that a decline in PA is prominent with age, and an increase in sedentary behaviors during adolescent years .…”
Section: Differences Between Latino and White Childrenmentioning
confidence: 99%
“…Despite these benefits, it has repeatedly been shown that children do not meet the recommended guideline of 60 min of physical activity per day [4,5]. To address this important public health issue, over the past couple of decades, school-based physical activity interventions have been a popular strategy to facilitate children meeting the 60-min per day guideline and to develop the knowledge and skills to be physically active throughout their lifespan [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…1 Schools have a unique ability not only to address energy intake and nutrition, but also to help children meet minimum standards for daily engagement in health-enhancing physical activity (PA). 2,3 Research has shown that school-based PA interventions are effective for improving health outcomes and also for improving educationally relevant behavioral outcomes such as time on task [4][5][6] and academic achievement. 7,8 To experience optimal health benefits, it is recommended that children aged 6-17 years accrue at least 60 minutes of moderate to vigorous PA (MVPA) per day.…”
mentioning
confidence: 99%